The Burden of Respiratory Diseases among African Child Population: A Medical Geography Perspective - Hasna, M.H.P.; Ruzaik, Fareena (Department of Demography, University of Colombo, 2024)
Acute respiratory infections (ARIs) are a major contributor to child mortality in sub-Saharan Africa, particularly in East and Southern Africa, where the burden is disproportionately high. According to UNICEF's 2023 report, around 45 million children in these regions are affected by respiratory conditions, significantly impacting child health and survival rates. Pneumonia alone is responsible for 16% of all deaths in children under five, accounting for over 920,000 deaths globally in 2015. In Ethiopia, respiratory diseases affect 22% of children aged 12 to 23 months, and the under-five mortality rate due to pneumonia is among the highest globally, with 88 deaths per 1,000 live births. This research investigates the prevalence and impact of respiratory diseases on children in sub-Saharan Africa from a medical geographical perspective, using secondary data sources such as research articles, reports, and data from international organizations, including the World Bank and UNICEF. Quantitative data was analyzed using thematic analysis to identify major contributing factors to child mortality from respiratory diseases. Factors such as indoor air pollution, poor living conditions, urbanization, and environmental pollutants were identified as primary drivers.
Keywords: Child Population; Medical Geography; Mortality; Respiratory Diseases